How Awareness of Possible Evidence Induces Forthcoming Counter‐Interrogation Strategies1. Issue 6 (12th March 2014) - Luke, Timothy J.; Dawson, Evan; Hartwig, Maria; Granhag, Pär Anders; Granhag, Pär Anders; Vrij, Aldert; Meissner, Christian A.
Summary We propose that suspects' counter‐interrogation strategies vary as a function of their perception of the interrogator's knowledge about the events in question. The present study investigates the verbal behavior of guilty and innocent suspects when they are aware that there may be incriminating evidence against them. Participants (N = 143) took part in either a simulated act of terrorism or a benign task. They were then interviewed about their activities. Participants were randomly assigned to receive no additional information or to be informed that an investigative team may have collected evidence from surveillance cameras. Results suggest that when alerted to possible evidence against them, guilty suspects adopt either extremely withholding or extremely forthcoming verbal strategies. Theoretical implications of these results are discussed. Copyright © 2014 John Wiley & Sons, Ltd.